PD-1, PD-L1 and PD-L2 Expression in Mantle Cell Lymphoma and Healthy Population - Karolová, Jana; Řádek, Martin; Helman, Karel; Špaček, Martin; Trněný, Marek; Klener, Pavel (Folia biologica (Praha), 2020)
Cell surface expression of PD-1, PD-L1 and PD-L2 immune checkpoints on B and T cells obtained from patients with mantle cell lymphoma shows ambiguous results across many studies and creates obstacles for the implementation of immune checkpoint inhibitors into the therapy of mantle cell lymphoma. Using multiparameter flow cytometry we analysed surface expression of PD-1, PD-L1 and PD-L2 molecules on B and T cells of 31 newly diagnosed mantle cell lymphomas and compared it with the results of 26 newly diagnosed chronic lymphocytic leukaemias and 20 healthy volunteers. To gain insight into the age-dependent changes of surface expression of these immune checkpoints, flow cytometric subanalysis of 30 healthy volunteers of 25-93 years of age was conducted. Overall, we demonstrated weak surface expression of PD-1, PD-L1 and PD-L2 on B and T cells of mantle cell lymphoma patients (< 10 % when compared to healthy individuals). A significant age-dependent increase in the expression of PD-1 and its ligand PD-L2 was observed in healthy volunteers. Our results suggest that neither PD-1 nor its ligands represent relevant druggable targets for the therapy of mantle cell lymphoma. The observed age-dependent changes in healthy population could impact efficiency of immune checkpoint inhibitors and could be at least partly connected with increased incidence of cancer with age.
Keywords: dospělí; antigeny CD273; Adult; Programmed Cell Death 1 Receptor; B7-H1 Antigen; lidé; lymfom z plášťových buněk; studie případů a kontrol; Aged, 80 and over; Lymphoma, Mantle-Cell; T-lymfocyty; antigeny CD279; Case-Control Studies; Aged; Programmed Cell Death 1 Ligand 2 Protein; B-Lymphocytes; B-lymfocyty; antigeny CD274; lidé středního věku; senioři nad 80 let; senioři; T-Lymphocytes; Middle Aged; Humans